2016
DOI: 10.7717/peerj.2283
|View full text |Cite
|
Sign up to set email alerts
|

What are the probable predictors of urinary incontinence during pregnancy?

Abstract: Objectives. The frequency, predisposing factors and impact of urinary incontinence (UI) on quality of life (QoL) during pregnancy were investigated.Materials and Method. A preliminary cross-sectional survey was studied among pregnant women between January and July of 2014. A total of 132 pregnant women were recruited using a questionnaire form for sociodemographic features, the Turkish version of the International Consultation on Incontinence-Short Form (ICIQ-SF), for the characteristics of UI and Wagner’s Qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 43 publications
4
27
0
10
Order By: Relevance
“…There was no statistically significant difference between participants with and without urinary incontinence in terms of the last gestational period ( P = 0.331). Demircan et al . and Kılıç found results similar to the results of the present study …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was no statistically significant difference between participants with and without urinary incontinence in terms of the last gestational period ( P = 0.331). Demircan et al . and Kılıç found results similar to the results of the present study …”
Section: Discussionsupporting
confidence: 92%
“…Demircan et al . reported that 58.9% of pregnant women had mild UI, 7.1% had moderate UI, 7.1% had severe UI and 25% of the participants had UI several times a day . Wesnes et al .…”
Section: Discussionmentioning
confidence: 99%
“…The insinuation was that many of respondents that claimed to be nullipara could have had previous undisclosed parous experiences. It is hence not surprising that both age and parity were not significant predictors of UI in pregnancy in this study unlike previous studies . However, same observations were made about parity and women's age in Turkey and Ethiopia in which the findings were related to the difference in patients’ characteristics and health care system …”
Section: Discussionsupporting
confidence: 41%
“…Pregnancy and childbirth have been known to be risk factors for UI in women . Its prevalence in pregnancy ranged between 32% and 64% . In a multi‐ethnic study, highest incidence was found among the Europeans and North Americans (45.4%) while the lowest incidence was reported among Africans (25.5%) .…”
Section: Introductionmentioning
confidence: 98%
“…Although Demircan et al (12) discovered that age, number of pregnancies, and a history of abortion have predictive value for urinary incontinence during pregnancy, this is still some way removed from individualized risk prediction. Although Demircan et al (12) discovered that age, number of pregnancies, and a history of abortion have predictive value for urinary incontinence during pregnancy, this is still some way removed from individualized risk prediction.…”
Section: Introductionmentioning
confidence: 99%